2015
DOI: 10.1021/jacs.5b04613
|View full text |Cite
|
Sign up to set email alerts
|

Halide-Dependent Mechanisms of Reductive Elimination from Gold(III)

Abstract: Two unique organometallic halide series (Ph3P)Au(4-Me-C6H4)(CF3)(X) and (Cy3P)Au(4-F-C6H4)(CF3)(X) (X = I, Br, Cl, F) have been synthesized. The PPh3-supported complexes can undergo both Caryl–X and Caryl–CF3 reductive elimination. Mechanistic studies of thermolysis at 122 °C reveal a dramatic reactivity and kinetic selectivity dependence on halide ligand. For X = I or F, zero-order kinetic behavior is observed, while for X = Cl or Br, kinetic studies implicate product catalysis. The selectivity for Caryl–CF3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 40 publications
(39 reference statements)
8
74
0
5
Order By: Relevance
“…Aryl phosphonium salt was detected as the major product through 31 P NMR monitoring (see SI), which supports the oxidation of Au(I) to Au(III) and subsequent reductive elimination for the P-C bond formation. 17 These results confirmed that the synthetically appealing alkene dual functionalization could be achieved by simply using gold catalyst and base. To examine the generality of this reaction, we evaluated both oxy- and amino-arylation of alkene with this chemical activation strategy.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Aryl phosphonium salt was detected as the major product through 31 P NMR monitoring (see SI), which supports the oxidation of Au(I) to Au(III) and subsequent reductive elimination for the P-C bond formation. 17 These results confirmed that the synthetically appealing alkene dual functionalization could be achieved by simply using gold catalyst and base. To examine the generality of this reaction, we evaluated both oxy- and amino-arylation of alkene with this chemical activation strategy.…”
Section: Resultssupporting
confidence: 67%
“…This indicates a retained π-acidity of the Ar-Au(III) intermediate and highlights an interesting preference for the tandem cyclization/coupling over the P-Ar reductive elimination demonstrated in previous reports. 17 Reaction rate studies were then performed to analyze the effect of various catalyst permutations on the outcome of the reaction between 1a and diazonium 2a (Figure 3B). A difference in reaction rate was observed for different primary ligands with the order of reactivity being: ( p -Me-C 6 H 4 ) 3 PAuCl>PPh 3 AuCl>( p -CF 3 -C 6 H 4 ) 3 PAuCl.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested ac oncerted CÀC Figure 1. [169] Recent experimental observations by To ste'sg roup [171] and later our theoretical calculations [172] have unveiled that replacing of Fa toms attached to Au with other halides (X)c an strongly affect the rate of reductive elimination of CÀXa nd CÀ Cc oupling products from Au. Calculated activationfree energies (in kcal mol À1 )a re given in the parenthesis.…”
Section: Selectfluor As Asacrificial Oxidantina U I /Au Iii Catalysismentioning
confidence: 91%
“…4A) (40). Borane 2 was required for rapid reductive elimination to occur; in its absence, the intermediate [Au(III)]-F persisted for long enough to be observed by 19 F NMR spectroscopy, and side reactions arising from base-mediated decomposition or glass-etching occurred alongside slow reductive elimination, consistent with an outer-sphere mechanism for C-F bond formation assisted by 2 (4143). The combined protocol was directly translated to a radiological analog, affording the corresponding radiolabeled reductive elimination products starting from KF and Kryptofix [2.2.2], as shown in Fig.…”
mentioning
confidence: 89%